How to compute monofin's mechanical parameters? - Bideau, B.; Colobert, B.; Nicolas, G.; Legueroue, G.; Multon, F.; Delamarche, P. (2002)
Nowadays, finswimming is a recognised sport in full expansion. Equipment and technology evolution enables to improve swimmers performance. Russian swimmers during European championship in 1972 at Moscow were the first to employ monofins rather than twins-fins. Once again, it was Russians who were the first to use fibre-glass. Finswimming kinematic has been studied [1, 2] to optimise technique but the conception of monofins remains in great part empirical. The aim of this study is to show how monofins mechanical parameters could be computed. METHODS To study monofins` mechanical parameters, we have developed a device that allowed a quick release of monofins. A force plate was recording the force applied on the monofins. Simultaneously the Vicon system analysis (Vicon 370), made up of seven infrared cameras cadenced at 60 Hz, was able to record the three dimensional position of twenty markers stuck on the monofin. In this preliminary study, the monofin was considered as a rigid solid and characterised as damped harmonic oscillatory system. In this way the displacement of one marker was chosen to represent the solid. Also the system was characterised with a differential equation , x" + a.x` + b.x = 0, where a is the damping coefficient and b the rigidity coefficient. RESULTS Figure 1 shows the vertical displacement of the marker which represents the angular displacement of a monofin as a solid. The damping coefficient of this monofin was 0.75 and the elasticity coefficient was 0.31. DISCUSSION This preliminary study shows that it is possible to characterise monofins with two parameters. This way it seems possible to help a swimmer to choose a fin. As monofin can be evaluated, it appeared important to define the relationship between the swimmer and the fin. Moreover, an important population of monofins should be tested in order to optimise the conception of the monofin. Indeed, this kind of study could reveal the importance of the fibre employed.